Determinants of university alumni's intention to contribute to education waqf - Nurul Aien, Abd Aziz; Noraina Mazuin, Sapuan; Puteri Fadzline, Muhamad Tamyez (UiTM Publisher, 2024)
Financial resources are crucial for universities to sustain the operational and managerial costs encompassing academic and administrative aspects. The financial stability of a university is reinforced by the role and support of its alumni, who are perceived as potential contributors. Universities are increasingly focusing on financial sustainability through education waqf. Therefore, this study aims to explore the relationship between attitudes, subjective norms, perceived behaviour control, knowledge, and financial ability on the intention of university alumni to contribute to education waqf. Additionally, the study seeks to investigate how university alumni acquire information about these education waqf. A total of 175 respondents from Johor Bahru participated in the study. The results indicate that most university alumni become aware of education waqf through former university lecturers or administrators. Furthermore, the findings reveal that attitudes, subjective norms, knowledge, and financial ability influence university alumni's intention to contribute to education waqf. The findings of this study are valuable for universities in their efforts to increase the number of donors for education waqf and to ensure the sustainability of funds for the future.